PERFORMANCE ANALYSIS OF AN EXHAUST GAS RECIRCULATION SYSTEM UNDER INJECTION TIMING AND ENGINE SPEED VARIATIONS FOR EMISSION REDUCTION IN AN R180 DIESEL ENGINE - Muhammad Hubaisy Al Bara (Applied Science and Technology on Naval Engineering, 2026)
In efforts to comply with increasingly stringent environmental regulations, particularly those related to nitrogen oxide (NOx) emissions, exhaust emissions from conventional diesel engines remain a major concern. The Exhaust Gas Recirculation (EGR) system is one of the most widely developed emission control techniques, functioning to reduce combustion temperature by recirculating a portion of exhaust gases back into the combustion chamber. This study employs a simulation-based approach to investigate the impact of EGR implementation on the performance and emissions of an R180 diesel engine. The objective of this research is to analyze the effects of EGR application under variations in injection timing and engine speed. Ricardo WAVE software is used to model a one-dimensional (1D) single cylinder four stroke R180 diesel engine. Injection timing is varied at several crank angles before top dead center (BTDC), along with changes in engine speed. The evaluated parameters include nitrogen oxide (NOx), carbon dioxide (CO₂), hydrocarbon (HC) emissions, and brake specific fuel consumption (BSFC). The simulation results indicate that increasing the EGR rate significantly reduces NOx emissions due to a decrease in combustion temperature. However, under certain operating conditions, variations in injection timing and engine speed significantly influence the effectiveness of the EGR system. An appropriate combination of these parameters can achieve an optimal balance between emission reduction and engine performance. This study is expected to serve as a reference for developing simulation-based emission control strategies for conventional diesel engines, particularly for small-scale applications.